2005
DOI: 10.1103/physrevb.71.121404
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a rectifier with gold nanoclusters: X-ray reflectivity and atomic force microscopy measurements

Abstract: The prominent rectification property observed in these nano-structured films could be explained from the measured spatial asymmetry. An obvious application of this work will be to form an array of memory dots with gold nanoclusters by depositing these on a monolayer of organic molecules having desired "tail length".

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Introduction. -Chemically synthesized nanoparticles with a metal core surrounded by a dielectric ligand shell have received a lot of interest in recent years because of their unique electrical, magnetic and optical properties [1][2][3][4][5]. One of the major challenges to exploit these novel properties in nanotechnology is to form a dense monolayer film of these nanoparticles onto a chosen substrate.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Introduction. -Chemically synthesized nanoparticles with a metal core surrounded by a dielectric ligand shell have received a lot of interest in recent years because of their unique electrical, magnetic and optical properties [1][2][3][4][5]. One of the major challenges to exploit these novel properties in nanotechnology is to form a dense monolayer film of these nanoparticles onto a chosen substrate.…”
mentioning
confidence: 99%
“…It is also known that for a large ratio of metal core diameter to ligand shell thickness a hexagonal ordered phase is obtained in deposited monolayers [8,9]. But nanoparticles with smaller (few nanometers) diameter of metal core with organic capping of about 1 nm thickness, which exhibit interesting physical properties [1][2][3][4][5], do not exhibit long-range positional order and the coverage remains about 60% in the deposited monolayer films. Although several other techniques have been used earlier [8,10], perhaps the best method for formation of monolayer film of these smaller nanoparticles is to transfer the Langmuir monolayer of nanoparticles from the air-water interface to a substrate following Langmuir-Blodgett (LB) deposition technique [5,11,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the thiols induce changes in the electronic configuration of the NPs, increasing the hole density at the 5d Au level. [7][8][9][10][11][12][13] As a consequence of these changes in the electron configuration, the physical properties of the NPs change significantly; the most outstanding one is the ferromagneticlike behavior of thiol-capped Au NPs despite the diamagnetic character of bulk gold. 9 Thiol-capped Au NPs also exhibit a wider SPR than bare NPs, which is associated with an extra dampìng due to the interaction of conduction electrons with the thiols.…”
mentioning
confidence: 99%